The Relationship between Nutritional Intake and Obesity in Children during the Covid-19 Pandemic - Mahjuri Mahjuri; Suryana Suryana; T Khairul Fajri; Agus Hendra Al Rahmad (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2021)
The Covid-19 pandemic has affected school children who are not homeschooled. Moreover, the pandemic has negatively impacted their food intake, sleeping behavior, and physical activities; these impacts lead to obesity. This study aims to (1) describe the children's intake of energy and nutrients (KH, protein, and fat) that cause obesity during the 2021 Covid-19 pandemic, (2) describe the incidence of obesity in children during the 2021 Covid-19 pandemic, and (3) analyze the relationship between food intake and the incidence of obesity in children during the 2021 Covid-19 pandemic. This study employed a quantitative design with a cross-sectional approach. The researchers investigated the relationship between energy, carbohydrate, fat, and protein intake and obesity in children. This research was conducted at Raudhatul Mubarakah Islamic Boarding School from 31 August to 6 September 2021. This study has discovered that most of the respondents (78%) have insufficient energy intake, 23 samples (46%) have insufficient carbohydrate intake, 39 samples (78%) have insufficient fat intake, and 20 samples (40%) have sufficient protein intake. Moreover, this study has found that 22 samples (44%) are obese while 28 samples (56%) are not obese. Finally, this study has proven a relationship between protein intake and the incidence of obesity (p < 0.05). Meanwhile, energy, carbohydrate, and fat intakes do not show significant relationships with the incidence of obesity (p > 0.05).